Prospective study on the knowledge and practice of foot care among diabetic patients - Manjunath, Meghana; T., Nandini (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The magnitude of diabetic foot ulcers (DFUs) and the amputation rates due to DFUs are high in India. Proper diabetic foot care can minimize these rates. Although numerous such studies have been done, reinforcement of awareness to practice diabetic foot care is necessary to reduce the incidents of DFUs. Methods: 134 voluntary participants from SSMC, Tumkur and Karnataka Institute of Endocrinology and Research, Bangalore were included following ethical clearance. The patients were requested to fill the validated knowledge and practice questionnaire which were presented to them in their own language. Demographic details of the participants were also collected. The responses were recorded and statistically analyzed. A score of >70% was gauged as good, 50 to 70% as satisfactory and <50% as poor. Results: Of the 134 participants, 73.13% had good knowledge on foot care, 22.8% had good foot care practice and 73.13% had a satisfactory practice score. Patients with history of foot ulcer had a mean score (±SD) of 12.75 (±1.91) knowledge score and 47.75 (±6.05) practice score which is lower compared to those without history of ulcers, 13.86 (±2.37) and 55.40 (±6.88) respectively. Patients from urban and rural areas had about the same mean scores, 13.51 (±2.50), 54.98 (±6.83) and 13.30 (±2.60), 54.73 (±7.49) (knowledge, practice score) respectively. Conclusions: Foot care among diabetics is only satisfactory and has to be improved. Knowledge is the key to better practice so early diagnosis, repeated counselling, regular follow ups and good sugar control is necessary to reduce incidents of DFUs.